R-peaks detection based on stationary wavelet transform. Issue 3 (October 2015) - Merah, M.; Abdelmalik, T.A.; Larbi, B.H.
Highlights This work makes a R-peaks detection based on stationary wavelet transform (SWT). It has the same sampling time of the signal. It inherently leads to more accurate estimation of the QRS fiducial points. It detect R peaks over different types of arrhythmias and types of noise. Only one scale of SWT is applied, in order to reduce the computational complexity.